(untitled) (Research, Society and Development, 2021)
This integrative review aimed to compare endodontic treatment in a single session with that carried out in multiple sessions, seeking scientific evidence regarding the reduction of postoperative complications such as pain, retreatment, reduction of bacteria and effectiveness of endodontic treatment in a single session. The study was carried out through a bibliographic survey in Pubmed and SciELO databases with manuscripts published between 2017 and 2021, using the following keywords: “Endodontics”; “Treatment of the Root Canal”; “Single session”, with the help of the Boolean operator “AND”. A total of 123 articles were found, where 39 were evaluated based on the inclusion criteria: Studies that evaluated endodontic treatment in a single session, studies published in the last 05 years, and as exclusion criteria: Articles not related to the topic, in addition to course completion papers, thesis and dissertations, resulting in 5 articles used for this review. The literature shows that the treatment of the root canal in a single session, performed with a good technique, brings efficient results, however, some studies have shown conflicting results. if that the techniques are operator-dependent. In elements with a high infection rate, the results are conflicting, with some sources presenting effective results with the treatment in a single session, regardless of the state of the approached element, and others presenting advantages in a multiple session approach, when it presents septic content. Thus, further clinical studies are needed to compare the two techniques, to determine clear indications for each of them.